MANFAAT KAMPANYE ANTI ROKOK DI MEDIA SOSIAL DALAM MEMPENGARUHI NIAT BERHENTI MEROKOK - Shalikhatun Nurahmah; Didik Setyawan; Finisha Mahaestri Noor (Conference on Innovation in Health, Accounting and Management Sciences (CIHAMS), 2020)
This study aims to examine the benefits of anti-smoking campaigns on social media in influencing smoking cessation intentions. The high use of social media can contribute by posting messages that persuade to reduce cigarette consumption which tends to increase. The data was collected through a questionnaire that was distributed online to several provinces in Indonesia. The sampling technique used is probability sampling and Hypothesis testing is carried out by regression using Structural Equation Modeling with Amos Application The results in this study indicate that all hypotheses are supported. This statement can be inter preted that the antecedent variables of perceived usefulness in the form of messages, content or content, and media credibility require the perception of benefits as forming the intention to quit smoking.